2020
DOI: 10.1101/2020.02.13.948026
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emerging viruses in British Columbia salmon discovered via a viral immune response biomarker panel and metatranscriptomic sequencing

Abstract: The emergence of infectious agents poses a continual economic and environmental challenge to aquaculture production, yet the diversity, abundance and epidemiology of aquatic viruses are poorly characterised. In this study, we applied salmon host transcriptional biomarkers to identify and select fish 25 in a viral disease state but only those that we also showed to be negative for established viruses. This was followed by metatranscriptomic sequencing to determine the viromes of dead and dying farmed Atlantic (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 90 publications
0
19
0
Order By: Relevance
“…In fact, specific gene expression signatures of infection are being identified using this approach (Miller et al 2017). Integration of pathogen and host gene profiling may represent a better non-lethal approach-particularly for systemic infections that often occur with viral diseases-and potentially requires only a small amount of gill tissue (Mordecai et al 2019(Mordecai et al , 2020.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, specific gene expression signatures of infection are being identified using this approach (Miller et al 2017). Integration of pathogen and host gene profiling may represent a better non-lethal approach-particularly for systemic infections that often occur with viral diseases-and potentially requires only a small amount of gill tissue (Mordecai et al 2019(Mordecai et al , 2020.…”
Section: Data Collectionmentioning
confidence: 99%
“…This was the first program of its kind to explore a broad base of potential pathogens (viruses, bacteria, fungal, and protozoan parasites) known or expected to cause disease in salmon worldwide, and the interplay between wild and cultured salmon (both aquaculture and enhancement hatcheries). Over 3 years, the SSHI screened 28,000 fish from wild, hatchery, and aquaculture settings for more than 60 potential pathogens (e.g., Nekouei et al 2018;Tucker et al 2018;Laurin et al 2019) and discovered several novel viruses (Mordecai et al 2019(Mordecai et al , 2020. Among this program's accomplishments were characterizing previously unrecognized diseases on salmon farms (Di Cicco et al 2017Cicco et al , 2018, developing a novel host biomarker panel that predicts the presence of a viral disease state in salmon (Miller et al 2017), and developing new in situ hybridization techniques to identify where infectious agents are occurring within diseased tissue (Di Cicco et al 2018).…”
Section: Case Study 2-using Novel Approaches To Study Infectious Agenmentioning
confidence: 99%
“…Additionally, and perhaps suggesting that the diversity in the marine environment is not yet fully understood, a Nidovirus (PsNV) recovered from Pacific Salmon shares greater similarity with coronaviruses than to other fish or invertebrate nidoviruses. Interestingly, PsNV was localized via in situ hybridization to gill tissue, suggesting a similar tissue tropism and infection strategy to other respiratory coronaviruses (Mordecai et al, 2019(Mordecai et al, , 2020. The morphology, genome organization, and replication of marine gammacoronaviruses is highly similar to human coronaviruses (Mihindukulasuriya et al, 2008;Woo et al, 2014).…”
Section: Marine Coronavirus Diversitymentioning
confidence: 87%
“…Miller et al (2017) demonstrated that the detection of a viral disease state in salmon could be accomplished by the co-regulation of as few as seven biomarkers. This approach has led to the discovery of several novel viruses in salmon (Mordecai et al 2020) and the elucidation of the developmental pathway of a natural disease outbreak, from a viral carrier state to disease causing death (Di Cicco et al 2018). Recently, salmonid biomarker panels have been developed and validated for the detection of thermal and salinity stress (Akbarzadeh et al 2018;Houde et al 2019a), but the identification of a panel specific to hypoxic stress activated in gill tissue has proven to be more difficult.…”
Section: Introductionmentioning
confidence: 99%